Preliminary results of phage display method to produce recombinant anti-schistosoma mansoni antibodies - dos Santos Cosac, Danielle Cristina; Cardoso, Fernando Manuel Henriques; de Melo, Tiago; Machado Carlos Ferreira, Pedro Manuel (Revista de Patologia Tropical / Journal of Tropical Pathology, 2024)
Schistosomiasis is a parasitic disease caused by trematodes of the genus Schistosoma. It is a neglected tropical disease, in which almost 240 million people are infected worldwide and about 700 million are at risk of acquiring the infection. The transmission has been reported in 78 countries. An accurate diagnosis of schistosomiasis is essential for treatment and disease control programs. However, diagnostic techniques may have some sensitivity limitations, especially in mild infections, with low egg elimination rates. Therefore, the present study aims to select recombinant antibodies against Schistosoma mansoni antigens to be applied in the serodiagnosis of schistosomiasis in the future. Adult parasites of S. mansoni were extracted by perfusion of the liver of infected mice. The recombinant antibody methodology was based on Phage Display, involving 3 rounds of selection by Biopanning. The visualization of the antigen-antibody binding was performed through Indirect ELISA test. The first two selection rounds of Biopanning showed positive values for the presence of phages, but the third cycle did not generate a significant amount of phage particles. For the indirect ELISA test, 15 male and 15 female clones were selected. It was observed that most of the antibodies reacted similarly to both male and female antigens. This work has provided valuable information that could be useful for the development of diagnostic technologies for Schistosomiasis. KEY WORDS: Schistosomiasis; Schistosoma mansoni; antibodies; bioprospecting